Fault Location Scheme for Over-Zone Feeding Operation Condition on High-Speed Railway - Lin, Guo-song; Quan, Wei; Tong, Xiao-yang (Journal of electrical engineering & technology, 2022)
Cross-coupling autotransformer (AT) feeding system is applied on high-speed electrified railways in China. According to operation requirement, ‘over-zone feeding operation condition’ exists. When fault occurs on this operation condition, the fault location system should adjust its original scheme to adapt. We analyzed the shortcoming in traditional fault location of this feeding mode. Analysis indicates that when fault occurs in the non-over-zone section, fault location can be well done by existing principle and when fault occurs in the over-zone section, a new fault location scheme must be proposed. Based on the analysis of circuit networks of over-zone section in this feeding mode, the feeder current ratio of up line and down line in sectioning post (SP) is derived when fault occurs in section from SP to AT post 2 (ATP2) and the port impedance at ATP2 is derived when fault occurs in section from ATP2 to substation 2 (SS2). A reasonable fault location scheme was proposed for over-zone section based on feeder current ratio method of up line and down line and port impedance method in this paper. The simulation results based on Matlab/Simulink showed that when fault occurs on over-zone section the fault position can be located accurately according to this novel fault location scheme.